The N-Terminal Region of Plasmodium falciparum MSP10 Is a Target of Protective Antibodies in Malaria and Is Important for PfGAMA/PfMSP10 Interaction - Nagaoka, Hikaru; Kanoi, Bernard N.; Jinoka, Kana; Morita, Masayuki; Arumugam, Thangavelu U.; Palacpac, Nirianne M. Q.; Egwang, Thomas G.; Horii, Toshihiro; Tsuboi, Takafumi; Takashima, Eizo (Frontiers in Immunology, 2019)
Clinical manifestation of malaria is mainly due to intra-erythrocytic development of Plasmodium parasites. Plasmodium falciparum merozoites, the invasive form of the blood-stage parasite, invade human erythrocytes in a complex but rapid process. This multi-step progression involves interactions between parasite and human host proteins. Here we show that antibodies against a vaccine antigen, PfGAMA, co-immunoprecipitate with PfMSP10. This interaction was validated as direct by surface plasmon resonance analysis. We then demonstrate that antibodies against PfMSP10 have growth inhibitory activity against cultured parasites, with the region PfMSP10 R1 that is critical for its interaction with PfGAMA being the key target. We also observe that the PfMSP10 R1 region is highly conserved among African field isolates. Lastly, we show that high levels of antibodies against PfMSP10 R1 associate with reduced risk to clinical malaria in children resident in a malaria endemic region in northern Uganda. Put together, these findings provide for the first-time the functional context of the important role of PfGAMA/PfMSP10 interaction in erythrocyte invasion and unveils a novel asexual blood-stage malaria vaccine target for attenuating P. falciparum merozoite invasion.